Optimasi Formula Nanohydrogel Icariin Sebagai Afrodisiak.: Optimization of Icariin Nanohydrogel Formula as an Aphrodisiac - Tajudin, Tatang; Indratmoko , Septiana; Prawatya, Adecya Nur (Jurnal Tumbuhan Obat Indonesia, 2023)
Decreased sexual desire is a type of sexual dysfunction that is common in men. Sexual dysfunction can be controlled by using herbs that have activity as aphrodisiacs. Many herbs are efficacious as aphrodisiacs, one of which is the icariin compound from the epimedium plant. However, the use of oral drugs must go through absorption and distribution processes to cause pharmacological effects, besides that the first pass effect that occurs in the liver reduces the bioavailability of the drug. This study aims to optimize the icariin nanohydrogel formula for use as a topical aphrodisiac, preparation characteristics, and the effect of nanohydrogel on the diffusion of icariin compounds. Formula optimization was carried out using the Simplex Latice Design (SLD) method with variations of carbopol, HPMC and TEA. Quantitative data analysis of aphrodisiac activity was analyzed by One Sample T-Test. The optimal formulation is obtained at a ratio of 1.415 (carbopol) : 2.168 (HPMC) : 1.208 (TEA), resulting in a clear, cucumber fish oil-scented preparation that is stable, with a viscosity of 19753.3 cps and an adhesive force of 0.387 seconds, pH 6.1, as well as a spreading power with a diameter of 5.56 cm. The hedonic test conducted on 4 formulas with the addition of fragrance shows that formula 3 is preferred by the respondents, followed by formula 4, formula 2, and formula 1. The cumulative amount of the penetrated preparation is 0,174 µg/cm2 at 10 minutes, 0,283 µg/cm2 at 15 minutes, 0,398 µg/cm2 at 30 minutes, 0,498 µg/cm2 at 60 minutes, and 0,603 µg/cm2 at 120 minutes.